2000
DOI: 10.1046/j.1365-2036.2000.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent symptoms and gastro‐oesophageal reflux disease in patients with duodenal ulcer treated for Helicobacter pylori infection

Abstract: Background: Eradication of Helicobacter pylori has been shown to prevent relapse of endoscopically detected duodenal ulcers. There is controversy regarding symptom improvement after therapy. Some studies have suggested that a substantial number of patients remain symptomatic after eradication therapy. Other studies suggest that gastro‐oesophageal reflux disease (GERD) may develop as a result of H. pylori eradication. Aim: To determine the relationship between symptoms and H. pylori eradication and to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
1
12

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 20 publications
2
70
1
12
Order By: Relevance
“…Case-control studies (9,11,14) have shown that the eradication of H. pylori from patients with duodenal ulcers may provoke GERD. This finding, however, has not been confirmed by other investigators (23,24). Conflicting data have been also observed in studies evaluating the association between GERD and H. pylori infection.…”
contrasting
confidence: 51%
“…Case-control studies (9,11,14) have shown that the eradication of H. pylori from patients with duodenal ulcers may provoke GERD. This finding, however, has not been confirmed by other investigators (23,24). Conflicting data have been also observed in studies evaluating the association between GERD and H. pylori infection.…”
contrasting
confidence: 51%
“…26 Two randomized controlled trials in 603 individuals reported on the development of oesophagitis. The development of reflux symptoms was uncommon, occurring in 6% of individuals undergoing eradication and 3% taking placebo (relative risk: 2, 95% CI: [1][2][3][4][5]. Differences between these studies are probably related to the small sample sizes, which make it difficult to detect an uncommon event, differences in the pattern of gastritis in the different populations studied and the lack of a randomized control group in others.…”
Section: Discussionmentioning
confidence: 92%
“…2 The incidence of symptomatic or endoscopic GERD developing in ulcer patients cured of the infection, however, has ranged widely in other reports. [3][4][5][6][7] The results of H. pylori eradication in non-ulcer dyspepsia have been mixed, with some studies showing no benefit and others demonstrating improvement in symptoms and prevention of future ulcer disease. [8][9][10] A recent meta-analysis demonstrated modest efficacy for H. pylori eradication in alleviating dyspeptic symptoms with a number needed to treat of 19. 11 A subsequent meta-analysis using individual patient data suggested that the benefit of eradication was similar whether patients with predominant epigastric pain or predominant heartburn were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies made evident that the virulence of the CagA-positive H. pylori strains can determine a protector effect against the development of reflux esophagitis, especially that more severe (18,39) , including Barrett's esophagus (37) .…”
Section: Discussionmentioning
confidence: 99%